2000
DOI: 10.1017/s0025315400003118
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of shell utilization and selection in two sympatric hermit crabs (Anomura: Diogenidae) in south-eastern Brazil

Abstract: The present study evaluated shell utilization and preference of two sympatric hermit crab species, Calcinus tibicen and Clibanarius antillensis, from Ilha Galheta de Dentro, Vitória Bay, south-eastern Brazil. Distribution of individuals and use and availability of shells were estimated in the field, where micro-habitat and shell partitioning were demonstrated between the two species of crabs. Calcinus occurred in higher numbers in the infralittoral fringe and shallow subtidal, while Clibanarius was found mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 22 publications
1
28
0
1
Order By: Relevance
“…Secondly, the occupation of a specific shell is influenced either by the interactions among hermit crabs, such as intra-specific competition for the shell, or by other resources (Bertness 1980, Gherardi and Nardone 1997, Dominciano and Mantelatto 2004, Sant'Anna et al 2006b), coexistence of different hermit crabs species (Kellog 1977, Bertness 1980, Gherardi and Nardone 834 SARA R. SAMPAIO and SETUKO MASUNARI 1997, Floeter et al 2000, Turra 2003, Sant'Anna et al 2006b), predation (Bertness 1982, Rotjan et al 2004), presence of gastropods in the community (Bertness 1980, Turra and Leite 2001, Sant'Anna et al 2006a, previous experience (Hazlett 1993, Hahn 1998, Meireles et al 2008, Alcaraz and Kruesi 2009) and formation of aggregations (Hazlett 1981, Turra andLeite 2000a). The hermit crab ability in detecting odours of died or dying gastropods was also reported (Kratt andRittschof 1991, Chiussi et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the occupation of a specific shell is influenced either by the interactions among hermit crabs, such as intra-specific competition for the shell, or by other resources (Bertness 1980, Gherardi and Nardone 1997, Dominciano and Mantelatto 2004, Sant'Anna et al 2006b), coexistence of different hermit crabs species (Kellog 1977, Bertness 1980, Gherardi and Nardone 834 SARA R. SAMPAIO and SETUKO MASUNARI 1997, Floeter et al 2000, Turra 2003, Sant'Anna et al 2006b), predation (Bertness 1982, Rotjan et al 2004), presence of gastropods in the community (Bertness 1980, Turra and Leite 2001, Sant'Anna et al 2006a, previous experience (Hazlett 1993, Hahn 1998, Meireles et al 2008, Alcaraz and Kruesi 2009) and formation of aggregations (Hazlett 1981, Turra andLeite 2000a). The hermit crab ability in detecting odours of died or dying gastropods was also reported (Kratt andRittschof 1991, Chiussi et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Among these characteristics are weight (Hahn 1998, Dominciano and Mantelatto 2004, Turra and Leite 2004, size (Bertini andFransozo 2000, Turra andLeite 2004), opening size (Botelho and Costa 2000, Bertini and Fransozo 2000, Sant'Anna et al 2006a) and architecture and volume (Gherardi and Nardone 1997, Floeter et al 2000, Shih and Mok 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative shell characters were measured and examined, including shell length (SL) and width (SW), weight (WW), internal volume (SIV), aperture length (SAL) and width (SAW). The internal volume of shells was evaluated using a graduated syringe (Floeter et al, 2000). All quantitative measurements were recorded to the nearest 0.01 mm for size using digital vernier calipers, 0.01 g for weight using digital weighing scales, and 0.1 ml volume using graduated syringes.…”
Section: Specimen Sampling and Analysismentioning
confidence: 99%
“…The variability in shell use by hermit crabs is thought to be influenced by environmental factors such as shell availability (Bertness 1980, Leite et al 1998), but crab preferences may also be important (Floeter et al 2000, Turra & Leite 2002. Previous studies have demonstrated that past experience of hermit crabs with shells may lead to shell-related behavioral plasticity.…”
Section: Shell-species Selectionmentioning
confidence: 99%